SunStats: An IoT NodeMCU integrated web application with real-time energy monitoring and cost forecasting - Bilaw, Bernadette; Espenido, Luizabelle V.; Prillo, Rovie B. 4 0 16; 5 (2024)
u
Undergraduate Thesis: (Bachelor of Science in Information Technology) - Pamantasan ng Lungsod ng Maynila, 2024.
Keywords: 2 -- 0; 6; 20; 20; 2